Abortion in the first trimester: guideline of the DGGG (S2k-Level, AWMF Registry No. 015-094, December 2022) : part 1 with recommendations on care structures, information and advice on decision-making, measures before abortion and medical abortion = Schwangerschaftsabbruch im 1. Trimenon : Leitlinie der DGGG (S2k-Level, AWMF-Registernummer 015-094, Dezember 2022) : Teil 1 mit Empfehlungen zu Versorgungsstrukturen, Information und Beratung zur Entscheidungsfindung, Maßnahmen vor dem Schwangerschaftsabbruch und zum medikamentösen Schwangerschaftsabbruch - David, Matthias; Achtenhagen, Anne; Bamberg, Christian; Bormann, Cornelia; Felderhoff-Müser, Ursula; Groth, Sylvia; Hänel, Kristina; König, Klaus; Korell, Matthias; Michl, Susanne; Redler, Silke; Schleußner, Ekkehard; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Purpose: The aim was to develop evidence-based recommendations where possible. The guideline presents the medical principles and scientific evidence for indications, the counselling of affected women, performing terminations, the choice of method, and the care and monitoring of a terminated pregnancy up until week 12 + 0 of gestation p. c. Methods: In accordance with the requirements for S2k-guidelines, the contents of the guideline were drafted following a systematic search of the literature by a representative interdisciplinary group of experts. Guideline authors held several formal meetings under the auspices of the German Society for Gynaecology and Obstetrics (DGGG) during which the contents of the guideline were finalised and agreed upon. Recommendations: A total of 61 recommendations are provided, covering care structures, provision of information and counselling to support decision-making, the measures to be taken before terminating the pregnancy, and medical termination of the pregnancy.
Gesehen am 05.03.2023